'Writing about our adoption': A qualitative study on intercountry adoptive parents' narratives during the first post-adoption year. (July 2021) - Canzi, Elena; Molgora, Sara; Ferrari, Laura; Ranieri, Sonia; Mescieri, Lavinia; Rosnati, Rosa
Intercountry adoption requires adoptive parents to assume their parenthood as well as to acknowledge the cultural and ethnic origins of their child. Narratives are effective means to help individuals cope with non-normative transitions, including adoption, as they allow them to make sense of and legitimise their experiences. This qualitative study sought to extend knowledge about the value of using narrative methods with adoptive families to explore how the language they employ determines the ways in which they perceive situations and vice versa. It uses the word-driven textual analysis software T-LAB to identify key topics highlighted by parents and analyse them in relation to specific variables. Child characteristics, such as gender, age at adoption and birth country, and family variables, such as mother's and father's narratives and first or not-first parenting experience, were considered. From the 37 narratives sampled, those parents adopting from Asia and Eastern Europe, mothers and first-time parents faced the most challenges.